Online mathematics teacher education: Overview of an emergent field of research - Borba, Marcelo de Carvalho [UNESP]; Llinares, Salvador (Springer Nature, 2012)
Online mathematics teacher education is characterized as an emergent area of research in mathematics education. We identify some key topics that require further research: communities and networks of teachers in online environments; sustainability of these communities and kinds of organizational structures; knowledge-building practices in technology-mediated work group interactions; and online interactions among teachers. The emergence of new research issues also gives rise to new theoretical approaches or the adaptation of existing theoretical perspectives that are presented in this special issue. We summarize some of these theoretical perspectives and attempt to show how online environments have changed them, as well as some theoretical problems that remain to be solved.
Keywords: Communities and networks; Humans-with-media; Interaction; Mathematics teacher education; Mathematics teacher learning; Online professional development